2003
DOI: 10.1023/b:bile.0000003978.72266.96
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of winery effluent with upflow anaerobic sludge blanket (UASB) – granular sludges enriched withEnterobacter sakazakii

Abstract: Three upflow anaerobic sludge blankets (UASBs) were evaluated for the treatment of winery wastewater: the first was seeded with granular sludge enriched with Enterobacter sakazakii and reached a 90% COD removal within 17 d at hydraulic retention time of 24 h; the second was seeded with brewery granules and achieved 85% COD removal within 50 d, the third was seeded with just sludge and showed the typical problems encountered with conventional sludge seeding and had continuously to be re-seeded. A PCR-based tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 11 publications
1
48
0
Order By: Relevance
“…PCR was performed on 16S rRNA gene specific for Cronobacter sakazakii (20). Genomic DNA was extracted from overnight cultures.…”
Section: Pcr Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…PCR was performed on 16S rRNA gene specific for Cronobacter sakazakii (20). Genomic DNA was extracted from overnight cultures.…”
Section: Pcr Assaymentioning
confidence: 99%
“…PCR reactions were set in 25µL final volumes consisting of 5 µL of the bacterial genome DNA, 1 × buffer, 1.5 U Taq polymerase (Fermentas, Lithuania), 1.5 mM MgCl 2 , 0.8 mM dNTPs and 20 pmol primers each. Primers, Esak2-5 -CCC GCA TCT CTG CAG GAT TCT C-3 and Esak3 -5 -CTA ATA CCG CAT AAC GTC TAC G-3 were used (59°C annealing temperature) in PCR to amplify an 854 bp fragment to 16S rRNA gene (20). The PCR was carried out with initiation at 94°C for 5 minutes, then 30 cycles of denaturation at 94°C for 30 seconds, annealing at 59°C for 30 seconds and extension at 72°C for 2 minutes, followed by a terminal extension step of 72°C for 5 minutes.…”
Section: Pcr Assaymentioning
confidence: 99%
“…Four PCR primer pairs were used as given below, using 2.5 U GoTaq Flexi DNA polymerase enzyme (Promega Corporation, WI), 5x Green GoTaq Flexi buffer (Promega Corporation, WI), and a Genius thermocycler (Techne Ltd., UK). Keyser et al [19] primer pairs Esak2 and Esak3 were used to amplify an 850-bp PCR product the 16S rDNA gene. Lehner et al [20] primer pairs Esakf and Esakr were used to amplify 929-bp PCR product from the 16S rDNA gene.…”
Section: Polymerase Chain Reaction (Pcr) Probes For Cronobacter Spp mentioning
confidence: 99%
“…However 16S rRNA gene sequence analysis revealed that it was E. cloacae and had been misidentified. Several methods for the identification of E. sakazakii via PCR have been described and were used in this study (19,20,22). PCR products of the indicative size were obtained when genomic DNAs from E. sakazakii strains NCTC 11467 T and ATCC 12868 were probed as previously described.…”
Section: Patientsmentioning
confidence: 99%